REKONTRUKSI KURIKULUM MERDEKA BELAJAR DI SMK DARUNNAJAH BANJARMANGU KABUPATEN BANJARNEGARA PROVINSI JAWA TENGAH - Feri Tulistiyono; Rifqi Muntaqo (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2022)
The reconstruction of the independent curriculum is an effort to optimize the quality of education in Indonesia based on the interests and talents of learners. The "Merdeka Belajar" curriculum becomes an educational transformation with the hope that the outcomes of education in Indonesia will increasingly possess quality. The freedom in curriculum implementation provides various forms of flexibility to the curriculum being executed. The notion of curriculum freedom entails granting teachers the authority to incorporate local wisdom and encourage independent thinking among learners, allowing them to think freely without feeling confined to narrow perspectives. National education aims to enrich the nation's life and develop fully-rounded individuals, individuals who have faith and devotion to the One Almighty God and possess noble character. Education plays a pivotal role in Indonesia's future. The research method employed in this study is qualitative descriptive research. Data collection is done through observation, interviews, and documentation. This research falls within the category of a case study, aiming to provide an intensive, in-depth, detailed, and comprehensive examination of a case. The analysis involves several stages, including data collection, data processing, data presentation, and the final stage of drawing conclusions. The outcomes of this study include: 1) A curriculum design that applies a technology-based curriculum model (digital learning), 2) The implementation of the independent curriculum at SMK Darunnajah Banjarmangu, which was executed during the academic year 2022/2023 and adhered to vocational school standards by aligning 8 (eight) aspects of linking and matching, 3) A vocational subject block system.